Is It Possible to Increase Fertility in Latvia in the Near Future? - Komarova, Vera; Sondore, Anita; Čižo , Edmunds; Kokarevica, Anita (Socialinė teorija, empirija, politika ir praktika, 2024)
This article aims to study the medium-term fertility trend in Latvia answering the following research question: is it possible to increase fertility in the near future, as planned in the “Population Reproduction Strategy FAMILY – LATVIA – 2030 (2050)”? The authors analyzed the total fertility rate (TFR) in Latvia for the period of 1970–2022 (53 years). This interdisciplinary (demography, mathematics, economics, sociology) study applies mathematical analysis for investigating socio-demographic trends, as well as the theory of economic cycles for identifying demographic cycles and their phases in Latvia and forecasting fertility rate in the near future. Furthermore, the analysis of data from comparative sociological surveys helped the authors to understand the main reason for the decline in fertility in Latvia. This reason is value changes in society, in which the child is no longer at the center of the value system of men and especially women in Latvia. In turn, short-term ups and downs in fertility are determined mainly by socio-economic and political factors. Based on the results of differentiating the function of the total fertility rate (TFR) it can be expected that the decline in fertility in Latvia will continue for several more years before the bottom of the next demographic cycle is reached and there will be an upturn in a linearly declining fertility trend. Although, the upcoming bottom will be lower than the previous one, i.e. below 1.22–1.25 children on average per woman and the next peak will most likely be below 1.74. Thus, the increase in TFR in Latvia to 1.77 by 2027, planned in the “Population Reproduction Strategy,” is considered by the authors of this study to be absolutely unattainable.